Estimating the Economic Burden and Cost-benefit of Human Brucellosis Management under a One Health Framework in Occupationally Exposed Populations of Gujarat, India - Shroff, Sagar; Shazleen, M.; Aditi; Singh, Suman; Harikumar, A. V. (International Journal of Bio-resource and Stress Management, 2025)
The investigation was conducted during May–June, 2023 in 27 villages of Anand District, Gujarat, India to study the direct, indirect, and intangible costs associated with human brucellosis and evaluate the cost-benefit of a free treatment intervention implemented under a One Health framework. A retrospective, cross-sectional cost-of-illness study was conducted involving 50 individuals diagnosed with brucellosis. Participants were selected from four occupational categories: farmers, veterinarians, artificial insemination (AI) workers, and village resource persons (VRPs). Data were collected through structured interviews and categorized into direct costs (e.g., consultation, diagnostics, medicines, transportation), indirect costs (e.g., productivity losses), and intangible costs (e.g., mental stress, isolation), with all estimates reported in Indian Rupees (INR). Cost-benefit ratios (CBRs) were calculated using both average and median cost scenarios. Direct costs totalled to ` 319,598, with farmers incurring the highest burden. Indirect costs, largely due to productivity losses, amounted to ` 357,844, accounting for over half of the total disease burden. Mental distress was reported by 56% of respondents, highest among farmers (85.71%). Misdiagnosis was universal (100%) among those who sought initial treatment. The average CBR for the free treatment program was 2.9, indicating significant economic benefit. Median-based CBRs revealed the highest benefit for farmers (4.3) and VRPs (2.0), with lower returns for AI workers and veterinarians (1.1 each). Brucellosis imposes a substantial and uneven burden on rural occupational groups and this One Health model demonstrated strong cost-effectiveness and equity benefits. Broader implementation, along with early diagnosis and awareness efforts, is essential for effective disease control and livelihood protection.